High-P amphibolite-facies metamorphism in the Adrar–Souttouf Metamafic Complex, Oulad Dlim Massif (West African Craton margin, Morocco) - Molina, Jose Francisco (2018)
The Oulad Dlim Massif represents the northern segment of the Mauritanide belt that thrusts over the western margin of the Reguibat Shield, north of the West African Craton (WAC). This belt includes various metamorphic units of Archean, Neoproterozoic and Palaeozoic ages that were stacked and thrust eastward during the Variscan orogeny. The core of the Oulad Dlim Massif comprises the Adrar–Souttouf Metamafic Complex that represents a large tectonic unit made of high-grade mafic rocks and vast exposures of amphibolites. A characterisation of the metamorphism in these amphibolites is essential to understand the relationships of the Oulad Dlim Massif with the southern segments of the Mauritanide belt and to provide constraints on the geodynamic evolution of the western margin of the WAC. Here we determine the P–T conditions of metamorphism of two samples of garnet amphibolites collected at the northernmost end of the Adrar–Souttouf Metamafic Complex. The samples show a main mineral assemblage of garnet + low-Ti pargasite + oligoclase + phengite + epidote + quartz + rutile ± paragonite ± K-feldspar. We calculated their P–T conditions using the amphibole–plagioclase NaSi–CaAl exchange thermometer, and the garnet–amphibole–plagioclase–quartz and the amphibole–plagioclase Si–Al partitioning barometers. The thermobarometric results indicate that this mineral assemblage was formed at high-P amphibolite-facies conditions at 650–700 °C and 10–13 kbar. The observed stability of paragonite and phengite reveals fluid-absent conditions or the presence of a fluid phase with reduced H2O activity during the peak of metamorphism. We found no relicts of eclogite-facies mineral assemblage in the garnet amphibolites. This contrasts with the eclogite-facies metamorphism found due south in the Tarf Magneïna unit. This suggests that the northernmost end of the Adrar–Souttouf Metamafic Complex may have been buried to shallower depths than the units further south, probably during the Variscan orogeny. However, precise absolute radiometric dating of the high-P amphibolite-facies metamorphism is required to confirm these findings.